The use of synonyms in Abai’s “Words of wisdom” - Zhakupov, Ж.А.; Shaimerden, Г.Т. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
This article discusses the use of synonyms in Abai's "Words of wisdom". The article uses methods of analysis, synthesis, description, contextual, semantic analysis. One of the most common artistic and linguistic qualities in Abai's retorts is his ability to use many synonyms very skillfully. They enhance the artistic essence of the Abai’s language and reveal its stylistic color. Stylistic use of synonyms in Abai's language: to reveal the expressive-emotional color of the work, to expand and supplement a certain concept; is used to generate gradation as a visual method. The first part of the article is guided by the work of scholars who studied Abay's prose. The main research section contains synonyms that can be found from the first word of Abai to the forty-fifth word of Abai. A semantic analysis of one of them is carried out, the nature of which as a synonym series is determined. In addition, the concept of "Man", which combines most of the synonyms encountered in the "Words of wisdom", is considered to be grouped into several semantic parts